Принципи архітектурного формування сільських садиб Волині ХІХ - поч. ХХ ст. та їх розвиток в сучасних умовах - Тарасюк, Іван Іванович; Tarasiuk, Ivan I. (Національний університет "Львівська політехніка", 2015)
Дисертація на здобуття наукового ступеня кандидата архітектури за спеціальністю 18.00.01 – Теорія архітектури, реставрація пам’яток архітектури. Національний університет "Львівська політехніка", 2015. Дисертація присвячена проблемі виявлення принципів архітектури сільських садиб Волині ХІХ – поч. ХХ ст. та їх розвитку в умовах сучасної України. На основі аналізу документальних, картографічних та іконографічних архівних матеріалів, а також натурного обстеження збережених сільських садиб історичної Волині ХІХ – поч. ХХ ст. створено багаторівневу типологічну класифікацію сільських садиб Волині, виявлено їх об’ємно-планувальні, композиційні, стилістичні характеристики, що сформувались під впливом комплексу різноманітних факторів. Виконане порівняння принципів архітектурного формування сільських садиб Волині ХІХ – поч. ХХ ст. із принципами розвитку сільських садиб інших регіонів України, внаслідок чого виявлені основні подібності та відмінності у об’ємно-просторових, композиційних та стилістичних ознаках. Висвітлені принципи архітектурної типології, композиції та стилістики сільських садиб, які є актуальними в умовах сучасного будівництва. The dissertation on receipt of scientific degree of candidate of architecture after specialty 18.00.01. – Theory of architecture, restoration of sights of architecture. National university " Lvivska politehnika", 2015. The Thesis is devoted to the problem of detection architectural principles of village’s country estates Volyn XIX century – beginning of the XX century and their development in the conditions of modern Ukraine. On the basis of analysis of the documentary, cartographic and iconographic archived materials, and also model inspection of the stored of country estates Volyn XIX century – beginning of the XX century. Created multilevel typology classification of village’s country estates Volyn, they are educed by volume of – plan, composition, stylistic description what formed under act of complex of various factors. In research comparison principles of the architectural of formation of village’s country estates Volyn XIX – beginning of the XX century with the principles of development of village’s country estates other regions of Ukraine. Basic similarities and differences are educed in by volume of-spatial, composition and stylistic sings. It is lighted up principles of the architectural typology, composition and stylistic of village’s country estates, and their development in the conditions of modern building.
Principles of architectural formation of village’s country estates Volyn XIX century - beginning of the XX century and their development in modern terms
Keywords: принципи архітектури сільських садиб; сільські поселення; архітектурно-планувальні рішення сільських садиб; типологія сільських садиб; традиційне народне зодчество; principles of architecture of village’s country estates; rural settlements; architectonically plan decision of country estates; typological of country estates; traditional folk architecture